ACURATE: A guide for reporting sham controls in trials using acupuncture - Ye-Seul Lee; Song-Yi Kim; Hyangsook Lee; Younbyoung Chae; Myeong Soo Lee (Integrative Medicine Research)
This paper presents the Acupuncture Controls gUideline for Reporting humAn Trials and Experiments (ACURATE) checklist, an extension of The Consolidated Standards for Reporting of Trials (CONSORT) and to be used along with STandards for Reporting Interventions in Clinical Trials of Acupuncture (STRICTA) when both real and sham acupuncture needles are used in the study. This checklist focuses on a clear depiction of sham needling procedures to enhance replicability and enable a precise appraisal. We encourage researchers to use ACURATE in trials and reviews involving sham acupuncture to assist reporting of sham acupuncture procedures and the related components.